THE EXISTENCE OF A COMPANY IN THE SOCIETY AND ITS LEGALITY IN INDONESIAN LAW (Journal of Private and Commercial Law, 2018)
The existence of a company, being an economic institution which has a multiplayer function, has become one of the main aspects of the societal and national lives because of the business activity conducted by the company. This situation has enabled the society to fulfil their needs, to conduct their economic activities, including the absorption of employment by the company which leads to the necessity of the legality of law in the law in Indonesia.